Introducing Anthropology (2nd editon) An Integrated Approach - Park, Michael Alan (McGraw -Hill, 2015)
Modern anthropology has become extraordinarily diverse, with a wide v ariety o f schools of th o u g h t and theoretical models within the discipline. N o t surprisingly, this b re ad th in the field has led to a range of ap p ro ach es to thinking ab o u t and teaching those courses traditionally called four-field introductions to anthropology. In short, we anthropologists each have sometimes very different answers to the question, What is anthropology?